A Proof-of-Concept Study on the Therapeutic Potential of Au Nanoparticles Radiolabeled with the Alpha-Emitter Actinium-225 - Evangelia-Alexandra Salvanou; Dimitris Stellas; Charalampos Tsoukalas; Barbara Mavroidi; Maria Paravatou-Petsotas; Nikolaos Kalogeropoulos; Stavros Xanthopoulos; Franck Denat; Gautier Laurent; Rana Bazzi; Stephane Roux; Penelope Bouziotis (MDPI AG, 2020)
Actinium-225 (225Ac) is receiving increased attention for its application in targeted radionuclide therapy, due to the short range of its emitted alpha particles in conjunction with their high linear energy transfer, which lead to the eradication of tumor cells while sparing neighboring healthy tissue. The objective of our study was the evaluation of a gold nanoparticle radiolabeled with 225Ac as an injectable radiopharmaceutical form of brachytherapy for local radiation treatment of cancer. Au@TADOTAGA was radiolabeled with 225Ac at pH 5.6 (30 min at 70 °C), and in vitro stability was evaluated. In vitro cytotoxicity was assessed in U-87 MG cancer cells, and in vivo biodistribution was performed by intravenous and intratumoral administration of [225Ac]225Ac-Au@TADOTAGA in U-87 MG tumor-bearing mice. A preliminary study to assess therapeutic efficacy of the intratumorally-injected radio-nanomedicine was performed over a period of 22 days, while the necrotic effect on tumors was evaluated by a histopathology study. We have shown that [225Ac]225Ac-Au@TADOTAGA resulted in the retardation of tumor growth after its intratumoral injection in U87MG tumor-bearing mice, even though very low activities were injected per mouse. This gold nanoparticle radiopharmaceutical could be applied as an unconventional brachytherapy in injectable form for local radiation treatment of cancer.